1986
DOI: 10.1128/jcm.23.5.970-972.1986
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase activity as a criterion for differentiation of oral mycoplasmas

Abstract: Phosphatase activity was found to be applicable as a criterion for the differentiation of Mycoplasma salivarium and Mycoplasma orale, predominant constituents of oral mycoplasmal flora. Therefore, a simple procedure for the phosphatase activity assay was established as a screening test for the differentiation of oral mycoplasmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…ACPs are found in mycoplasmas (16,17), but they have never been purified and characterized, probably because of uncertainty regarding the physiological importance. In this study, an ACP was purified from the membranes of M. fermentans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACPs are found in mycoplasmas (16,17), but they have never been purified and characterized, probably because of uncertainty regarding the physiological importance. In this study, an ACP was purified from the membranes of M. fermentans.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to uncertainty regarding their endogenous targets, physiological substrates. Previously, we demonstrated that ACP activity is present in some human-derived mycoplasmas and was higher in Mycoplasma fermentans, Mycoplasma faucium and Mycoplasma buccale than in the other mycoplasmas tested (17). Recently, a strain of M. fermentans has been implicated as a cofactor that would explain various puzzling features of infection by the human immunodeficiency virus (12,14).…”
mentioning
confidence: 95%
“…More recent results using a nested PCR reaction detected the organism in the synovial fluid of 23/25 (92%) of rheumatoid arthritis patients, and in 6/7 patients with other inflammatory arthritides, but not in 10 osteoarthritis patients, who do not have an inflammatory cell infiltrate. 29 Noda et al and Shibata et al 30,31 found that M. fermentans also had an acid phosphatase which would hydrolyse p-nitrophenol phosphate; its pH optimum was 5Á0.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 98%
“…However at pH 5Á0 the mycoplasma phosphatase activity against AMP remained almost the same, but was now 11% inhibited by b-glycerophosphate, and the mycoplasma showed some ability to hydrolyse p-nitrophenyl phosphate, indicating that acid phosphatase was present as previously reported. 30,31 It is possible that the only 60% inhibition of the mycoplasmal 5 0 N by AMPCP was a result of some residual acid phosphatase activity against AMP, which may well be a preferred substrate compared to b-glycerophosphate or p-nitrophenyl phosphate.…”
Section: The Nature Of the Induced Enzymementioning
confidence: 99%
“…We investigated whether Raytide phosphatase activity existed in other mycoplasmas. It was found that mycoplasmas possessing relatively higher levels of ACP activity (15) had higher levels of specific activity ( Table 2). Although ACPs are widely distributed in bacteria, very little is known about their physiological and pathological involvements.…”
mentioning
confidence: 99%